2019
DOI: 10.5194/se-2019-48
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating porosity estimates for sandstones based on X-ray micro-tomographic images

Abstract: We compare experimentally determined porosity with values derived from X-ray tomography for a suite of eight sandstone varieties covering a porosity range from about 3 to 25 %. In addition, we performed conventional stereological analysis of SEM images and examined thin sections. We investigated the sensitivity of segmentation, the conversion of the tomographic gray-value images representing the obtained X-ray attenuation coefficients into binary images, to (a) resolution of the digital images, (b) denoising f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…In general, the CMT method is fraught with some difficulties, considering high accuracy. Uncertainty of the results can result from the user or algorithm-defined value of threshold in image segmentation, beam fluctuations or hardening, and off-focal radiation [135]. The spatial resolution of CMT images is limited by X-ray energy, the number of pixels on the detector, and the diameter of the X-ray source.…”
Section: Methods Used To Assess Porosity In Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the CMT method is fraught with some difficulties, considering high accuracy. Uncertainty of the results can result from the user or algorithm-defined value of threshold in image segmentation, beam fluctuations or hardening, and off-focal radiation [135]. The spatial resolution of CMT images is limited by X-ray energy, the number of pixels on the detector, and the diameter of the X-ray source.…”
Section: Methods Used To Assess Porosity In Materialsmentioning
confidence: 99%
“…Hermanek and Carmignato [136], in studies on reference object with artificial defects, emphasized that voltage and current affect porosity, particularly for small defects. Nehler et al [135], in studies of sandstones, found that tomographic pore-volume quantification is imprecise, due to partly unresolved structures as compared to SEM images. Differences in linear attenuation and material porosity are influenced by the different composition of materials [137].…”
Section: Methods Used To Assess Porosity In Materialsmentioning
confidence: 99%
“…Moreover, a negative skewness in the histogram (Fig. 6) shows that the image resolution is not adequate to separate the pores from the matrix, i.e., the pores sizes are mostly below the image resolution (Nehler et al, 2019). This low resolution will increase the risk of underestimation (or overestimation) of porosity or other subsequent quantification on the binary images.…”
Section: Image Segmentationmentioning
confidence: 99%
“…Therefore, it comes as no surprise that several methods have been developed to estimate porosity in the past decades, including laboratory measurements (e.g., MAD and mercury intrusion porosimetry) and well-logging to imaging techniques. X-ray computed tomography (XCT) is a non-destructive and now a mature tool frequently used in porous media to characterize the hydraulic properties of samples such as porosity ( Van Geet et al, 2003;Taud et al, 2005;Nehler et al, 2019), pore geometry and structure (Mukunoki et al, 2016;Wildenschild & Sheppard, 2013), fracture network characterization, and permeability estimation (Okabe & Blunt, 2004;Ketcham et al, 2010;Mostaghimi et al, 2013;Peng et al, 2014). However, most of these studies were performed on sandstones or rocks with large grains rather than clays or clayey rocks having submicron feature size (i.e., grain or pore size) which is usually behind the resolution of most XCT instruments, and highresolution imaging is both expensive and time-consuming (Kaufhold et al, 2016).…”
mentioning
confidence: 99%
“…volume fraction of connected and isolated pores, shape, pore size, pore size distribution) [35]. The porosity evaluation using FIB tomography is relatively costly compared to Micro-CT and MIP techniques [36,37]. However, its high potential in analyzing the isolated pores and detecting finer pores can provide detailed information to reconstruct more actual 3D pore network.…”
Section: Introductionmentioning
confidence: 99%